CHEMICAL COMPOUNDS AND BIOLOGICAL ACTIVITY OF AN EXTRACT FROM BOUGAINVILLEA X BUTTIANA (VAR. ROSE) HOLTTUM AND STANDL - Guerrero, Rigoberto Villanueva; Vargas, Rodolfo Abarca; Petricevich, Vera L. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: A Bougainvillea x buttiana (var. Rose) Holttum and Standl extract (BxbREE) was prepared and its chemical composition, antioxidant and anti-inflammatory activity were evaluated. Methods: For the analyses of the phytochemical compounds present in BxbREE extract, gas chromatography-mass spectrometry (GC/MS) was used. To explore the anti-oxidant, anti-inflammatory activities, total phenolic contents, carbohydrates, lipids and carrageenan-induce paw edema models, respectively, were used. For in vivo experiments, the extract was orally, intraperitoneally and/or subcutaneously administered at doses of 0.04, 0.4, 4 and 40 mg/kg. Results: GC/MS analyses showed the presence of 7 compounds, including 2-Propenoic acid, 3-(2-hydroxyphenyl)-, (E)-(1.19%); 2-Methoxy-4-vinylphenol (0.22%); 3-O-Methyl-d-glucose (92.14%); n-Hexadecanoic acid (0.76%); Hexadecanoic acid, ethyl ester (1.17%); 9,12-octadecadienoic acid, ethyl ester (1.93%); and 9,12,15-Octadecatrienoic acid, ethyl ester (Z,Z,Z) (2.59%). Phytochemical qualitative analysis showed the presence of total phenolic contents at 320 mg of Gallic acid Equivalent/gram of dried extract (GA-Eq/g extract); carbohydrates 5.18 mg/ml and lipids 13.88 mg/ml. In accordance the structures the major compound was 3-O-Methyl-d-glucose. Our results also clearly indicate that BxbREE decreases inflammation in BALB/c mice as a subplantar injection of carrageenan-induced paw edema. The extract presented a potent dose-dependent inhibitory effect. The edema inhibition percentage was significantly lower in groups of animals treated with BxbREE by via intraperitoneal or subcutaneous when compared with those results obtained for groups treated by orally administration (p<0.001). Conclusion: In conclusion, this study established the anti-oxidant and anti-inflammatory activities of Bougainvillea x buttiana (var. Rose); also, this extract could be considered to be a natural anti-oxidant agent that represents an anti-inflammatory remedy.